Kontribusi Motivasi Kerja dan Peran Kepala Sekolah Terhadap Profesionalisme Guru SMA - Nurkolis Siri Kastawi; Agus Nugroho; Noor Miyono (Kelola: Jurnal Manajemen Pendidikan, 2021)
This study aims to determine the contribution of teacher work motivation to teacher professionalism, the principal's contribution to teacher professionalism, and the contribution of work motivation and the role of school principals to teacher professionalism. The population of the study was all civil servant teachers in SMA Negeri Salatiga with number of population 209 people and the sample are 131 people. The samples were chosen by using proportional random sampling technique. Data collection was done by distributing questionnaire and hypothesis testing with regression. The results showed, (1) there was a positive and significant contribution t of work motivation on teacher professionalism of 92.2%, (2)there was a positive and significant contribution of the role of the principal on the teacher professionalism of 90.2%, and (3) there was a positive and significant contribution of work motivation and the role of the principal on professionalism teachers at 93.1%. It is hoped that further research will find out other factors that contribute ot teacher professionalism.